2013
DOI: 10.1155/2013/174939
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and Efficient Synthesis of Silver Nanofluid Using Electrical Discharge Machining

Abstract: The electrical discharge machining (EDM) system has been proven feasible as a rapid and efficient method for silver nanofluid preparation. This study prepared the silver nano-fluid via EDM and investigated the relationship between its process parameters and product characteristics. The prior study had found that the silver nano-fluid prepared by EDM contained both silver nanoparticles and silver ions. Silver ions had revealed the cause of the high suspension of the silver nanoparticles. To examine the relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Advantages of ESDM are the following: the production process is conducted in dielectric fluid; thus, there will be no dust. It has rapid and mass preparation and is energy efficient, producing uniform particles [21]. The parameter settings for the nano-Ti colloid prepared by an electrical discharge machine in this paper are shown in Table 1.…”
Section: Electric Spark Discharge Methods (Esdm)mentioning
confidence: 99%
“…Advantages of ESDM are the following: the production process is conducted in dielectric fluid; thus, there will be no dust. It has rapid and mass preparation and is energy efficient, producing uniform particles [21]. The parameter settings for the nano-Ti colloid prepared by an electrical discharge machine in this paper are shown in Table 1.…”
Section: Electric Spark Discharge Methods (Esdm)mentioning
confidence: 99%
“…They found that machining time was three times faster than the conventional one. Tseng, Lee [102] in their work focused in the preparation of the silver nanofluid by the EDM system. They derived the relationship between the process parameters and product characteristics.…”
Section: Powder Mixed Edmmentioning
confidence: 99%
“…The system used intense energy to splatter the electrode surface in dielectric fluid, and this method has a wide application in the nanofabrication technology, for example, Ni-C powders in pure ethanol, silver nano fluid in ethylene glycol, gold nanoparticles in water or ethanol and carbon nanotubes (CNTs). Tseng, Lee [102] explained that for the nanofluid application issue, nanofluid must be strongly stable which does not sediment before any application or analysis but many other factors affect the stability of suspension such as concentration of particles, particle size in diameter, solution properties, electrical conductivity and pH. A. Singh [103] studied the surface characteristics with the use of mixed carbon nano tubes (CNTs) in EDM to obtain high surface finish value because of the high thermal conductivity of CNTs.…”
Section: Powder Mixed Edmmentioning
confidence: 99%
“…e production of nanosized metallic silver particles with different morphologies and sizes using different methods has been reported in previous studies, such as the electric spark discharge system (ESDS) [1][2][3]. PVA (Mw 89,000-98,000, 99+% hydrolyzed, 341584, 9002-89-5, MDL: MFCD00081922) was the eligible polymer since it stands out for its viscoelastic behavior, hydrophilicity, chemical stability [4] and biocompatibility [5].…”
Section: Introductionmentioning
confidence: 99%